L'Amerique Septentrionale suivant les Nouvelle Observations de Messrs. des l'Académie Royale des Sciences, etc. - Cóvens et Mortier (Chez Cóvens et Mortier, 1730)
Map shows southern and eastern portions of North America; Greenland, the islands of the Caribbean and New Spain; areas of Indian habitation, routes of exploration along Pacific coastline with dates. Includes illustration and notes. Relief shown pictorially. Scale not given.